2021
DOI: 10.1123/jsr.2019-0271
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps and Hamstring Strength Symmetry After Anterior Cruciate Ligament Reconstruction: A Prospective Study

Abstract: Objectives: To evaluate change in involved and uninvolved quadriceps and hamstring strength and limb symmetry indices (LSI) in regular intervals over the first 6 months following anterior cruciate ligament reconstruction (ACLR). Design: Prospective cohort study. Participants: Thirty-eight male participants (mean age: 24.2 [6.4] y, mean body mass index: 23.6 [4.2] kg/m2), who underwent ACLR were included. Main Outcome Measures: Isometric strength testing of the quadriceps and hamstring muscles was performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…35,36 Changes in strength AI were predominately achieved through changes in strength of the ACLR limb, as noted in recent literature assessing rehabilitation up to 6 months post-surgery. 37,38 Our findings extend upon these studies and suggest that the uninvolved limb may reasonably be used as a control when monitoring changes in muscle strength during later-stage rehabilitation.…”
Section: Changes In Isokinetic Strength Ai and Phase-specific Impulse...supporting
confidence: 72%
“…35,36 Changes in strength AI were predominately achieved through changes in strength of the ACLR limb, as noted in recent literature assessing rehabilitation up to 6 months post-surgery. 37,38 Our findings extend upon these studies and suggest that the uninvolved limb may reasonably be used as a control when monitoring changes in muscle strength during later-stage rehabilitation.…”
Section: Changes In Isokinetic Strength Ai and Phase-specific Impulse...supporting
confidence: 72%
“…Five studies discussed functional testing in ACL reconstruction recovery and rehabilitation [23][24][25][26][27] (Table VII). These studies compared the function and strength of injured and uninjured hip, quadriceps, and hamstring muscles 27 ; evaluated the use of LSI 24 and its alternatives 26 ; and cautioned against return-tosport criteria based on the achievement of stringent LSI values alone 23 . The authors of these studies suggested that there is benefit in integrating functional testing in return-to-sport criteria to assess the patient's return-to-sport potential and to predict a secondary injury and that hip external rotation is the only significant predictor of the hop test performance 25 .…”
Section: Hop Strength and Isokinetic Testingmentioning
confidence: 99%
“…The results of these tests assist in the identification of deficiencies in patients' muscular function or strength. Five studies discussed functional testing in ACL reconstruction recovery and rehabilitation [23][24][25][26][27] (Table VII). These studies compared the function and strength of injured and uninjured hip, quadriceps, and hamstring muscles 27 ; evaluated the use of LSI 24 and its alternatives 26 ; and cautioned against return-tosport criteria based on the achievement of stringent LSI values alone 23 .…”
Section: Hop Strength and Isokinetic Testingmentioning
confidence: 99%
“…A reduction in strength and neuromuscular coordination are associated with injury (Wilson et al 2020;Harput et al 2020;Ward et al 2015) and disease (Milosevic et al 2017;Stock et al 2019), whilst strength is a key quality of athletic performance (Joffe and Tallent 2020). Consequently, the enhancement of strength and neuromuscular coordination through maximising neurological adaptation is vital.…”
Section: Implications For Rehabilitation and Athletic Performancementioning
confidence: 99%